2004
DOI: 10.1016/j.visres.2004.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Wider recognition in peripheral vision common to different subtypes of dyslexia

Abstract: Italian children (n = 125) were classified into dyslexics, poor readers and ordinary readers. The dyslexics were further classified into the Boder and Bakker subtypes. The children were tested with the form-resolving field (FRF), which measures central and peripheral visual recognition. Dyslexics show higher correct identification of letters in the periphery, supporting the notion of a different distribution of lateral masking. A numerical characterization of individual FRFs--C2R--reliably distinguishes betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
44
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 39 publications
8
44
1
1
Order By: Relevance
“…Moreover, the lateral interference between adjacent letters (i.e., crowding; for a review, see Levi, 2008) is abnormal in dyslexia (Spinelli, De Luca, Judica, & Zoccolotti, 2002;Atkinson, 1991). In particular, dyslexics seem to have more crowding near the fovea than normal readers (Lorusso et al, 2004;Geiger & Lettvin, 1987). Recent studies show that crowding represents a limit for reading in skilled adults (e.g., Pelli et al, 2007).…”
Section: The Role Of Noise Exclusion Deficitsmentioning
confidence: 99%
“…Moreover, the lateral interference between adjacent letters (i.e., crowding; for a review, see Levi, 2008) is abnormal in dyslexia (Spinelli, De Luca, Judica, & Zoccolotti, 2002;Atkinson, 1991). In particular, dyslexics seem to have more crowding near the fovea than normal readers (Lorusso et al, 2004;Geiger & Lettvin, 1987). Recent studies show that crowding represents a limit for reading in skilled adults (e.g., Pelli et al, 2007).…”
Section: The Role Of Noise Exclusion Deficitsmentioning
confidence: 99%
“…Frequent-word reading is normally done by a rapid conversion of the visual word form to a lexical representation (Coltheart, 1978;Coltheart, Curtis, Atkins, & Haller, 1993). FWRI children are traditionally termed as "dyseidetics" (Boder, 1970;Lorusso, Facoetti, & Pesenti, 2004;Milne et al, 2003). It was assumed that they have a deficit in visual word Gestalt recognition (Boder, 1970) or some other visual deficit (Farmer & Klein, 1995).…”
Section: Diagnostic Subtypes Of Developmental Dyslexiamentioning
confidence: 99%
“…This is contrasted with poor response characteristics in the central visual field. Using Geiger's setup, another two studies confirmed that individuals with dyslexia have a broader peripheral vision (Lorusso et al, 2004;Perry, Dember, Warm, & Sacks, 1989). In terms of empirical evidence, only a few research studies have examined whether individuals with dyslexia have a better peripheral vision than normal readers.…”
Section: Dyslexia and Enhanced Peripheral Visionmentioning
confidence: 97%